Ferdinand De Saussure’s Syntagmatic And Paradigmatic Concepts of Charles Sander Peirce in The Quran On Qauliyah And Kauniyah Verses: Semiotics Approach - Abd. Shovy; Azmy, Lulu Ulul (Journal of Arabic Language Studies and Teaching, 2024)
This article aims to discuss semiotics with Ferdinand De Saussure’s syntagmatic and paradigmatic concepts and Charles Sander Peirce’s Grand Theory concept, with the object of study being qauliyah verses and kauniyah verses in the Koran and methodological reconstruction. This research method is qualitative with a library research method, namely looking for literature sources related to the discussion in the form of theses, dissertations, or other articles. The syntagmatic and paradigmatic concepts of Ferdinand De Saussure and Charles Sander Peirce’s Grand Theory, namely Semiotic analysis, seek to find a correlation between the meaning of something contained in something (text, sound, event). Semiotics means how humans interpret the things around them or the events of their lives. Augustine distinguishes natural signs from conventional signs; he mentions that they fulfill human psychological needs; they allow humans to describe and remember the world. It also makes the process of human thinking about life and signs about something that happens and moves beyond the realm of human rationality, which is spiritual. Meanwhile, natural signs are natural symptoms occurring around human life in various forms. This theory works by identifying, documenting, and classifying types of signs. The philosophers from the pragmatism school who formulated the semiotic discipline are Charles Sandres Pierce and Ferdinand De Saussure.